PEMANFAATAN BAHAN ORGANIK SEBAGAI BAHAN PEMBAWA INOKULAN FUNGI MIKORIZA ARBUSKULA - NURBAITY, ANNE; HERDIYANTORO, DIYAN; MULYANI , OVIYANTI (Jurnal Biologi Udayana; Vol 13 No 1 (2009): JURNAL BIOLOGI, 2009)
Arbuscular Mycorrhizal Fungi (AMF) is known as one type of biofertilizer. The carrier for this biofertilizer is usually made from inorganic material such as zeolite. Currently, it is important to find the alternative materials that can be used as biofertilizers’ carrier due to the need of lower cost and easily available, such organic matter. Rice straw and husk are some of the organic matter sources that can be used as a carrier of AMF. A glass house experiment was conducted to determine the effectiveness of different type of organic matter as a carrier of AMF’s inoculum. The experiment was arranged in factorial randomized block design with two factors, i.e. type of organic matter (zeolite as a control, straw, burnt-rice’s husk and combination of straw and rice husk 50/50 v/v) and type of different hosts of AMF’s (Jatropha sp. and Sorghum sp.). The results showed that application of burnt-rice’s husk was better carrier of AMF inoculum instead of straw or combination of straw and burnt-rice’s husk. The quality of AMF inoculum with burnt-rice’s husk as a carrier was as good as the control inoculum that used zeolite, in terms of the number of spores, the percentage of root colonization, root length colonized and root fresh weight. In summary, burnt-rice’s husk has a good potential carrier of AMF biofertilizer.
Keywords: arbuscular mycorrhizal fungi, biofertilizer, organic matter